Ti-in-zircon thermometry applied to contrasting Archean metamorphic and igneous systems - Hiess, Joe; Nutman, Allen P; Bennett, Victoria; Holden, Peter (Elsevier, 2015)
Ti-in-zircon thermometry with SHRIMP II multi-collector has been applied to two well-documented Archean igneous and metamorphic samples from southern West Greenland. Zircons from 2.71 Ga partial melt segregation G03/38 formed in a small (< 1 m3), closed